AUTISM AND INTERACTION: MULTIMODAL ANALYSIS OF PRACTICES LANGUAGE OF CHILDREN WITH THE ASD SPECTRUM - Rachida CHELLI (Universitaria Publishing House, Craiova, 2021)
This article revolves around the multimodality of oral language behavior (Mondada, 2008; Ferré, 2011) in autistic children. Successful communication for these children is a complex issue. This process aims to exchange with the others and transmit a message. Therefore, maintain relationships with receivers and weave affective and professional ties (Jackobson, 1663). Processes that children autistic people do not realize or at least find it difficult to establish. This, confirms that language proficiency is a fundamental element in the development of the child's personality; of its success and its integration into society. Therefore, to understand the language mechanism in children with the ASD spectrum (Rousselle, 2009) from a dynamic perspective, it is necessary to take into account the interactions between the different linguistic modalities. Our contribution is a part of the psychology of communication (Abric, 2019) and interactional linguistics (Kerebrat-Orecchioni, 2005).